International climate policy leadership after COP23: The EU must resume its leading role, but cannot do so alone - Susanne Dröge; Vijeta Rattani (Stiftung Wissenschaft und Politik (SWP), 2018)
The net outcome of the Bonn climate talks (23rd Conference of the Parties, COP23) in November was lukewarm at best. Many technical issues were brought forward and the political risks caused by the US announcement to pull out of the Paris Agreement were kept at bay. Yet, leadership to fill the void left by the US was lacking. Germany, who was co-hosting with the Fiji Islands, could not table ambitious solutions as in November 2017 it only had a caretaker government in place. The Fiji Presidency brought attention to adaptation, agriculture, finance and the loss and damage debates, but could not succeed to the full extent, mainly due to conflicts on finance. The performance by China was disappointing as it did not follow up on its ambitions to lead. With a view to 2018, the EU once again claimed a leadership role on the international climate agenda, though not unilaterally. During the Bonn UNFCCC negotiations, however, the EU disappointed many of its partners as it did not deliver as a constructive negotiator and bridge builder. Rather, it pushed for some of the technical issues. Given the urgency to forge a rulebook for the Paris Agreement implementation and in light of progressing climate change, the EU and its Member States need to demonstrate instrumental and directional leadership in the run-up to the next COP in Katowice, Poland in 2018.
Keywords: 320